Cerebro-Cerebellar Networks in Migraine Symptoms and Headache - Noseda, Rodrigo (Frontiers in Pain Research, 2022)
The cerebellum is associated to the biology of migraine in a variety of ways. Clinically, symptoms such as fatigue, motor weakness, vertigo, dizziness, difficulty concentrating and finding words, nausea and visual disturbances, are common in different types of migraine. The neural basis of these symptoms is complex, not completely known, and likely involve activation of both specific and shared circuits throughout the brain. Historically, ischemic stroke involving the posterior circulation or neurosurgical removal of tumors in humans, provided the fundamental knowledge to theorize about the functions of the cerebellum. Anatomical tract-tracing studies in non-human primates, cats and rodents, built upon and expanded its role and connectivity within the brain. Consequently, and given the intriguing structure of the cerebellum, featuring modular organization and computational functionality, an impressive number of theories were proposed over the decades to explain its fundamental role. Nowadays, with the addition of functional imaging, much progress has been done on cerebellar structure and function in health and disease, and as a consequence, the theories refined. Accordingly, it has been proposed that the cerebellum is useful but not necessary for the execution of motor, sensory or cognitive tasks, but rather would participate as an efficiency facilitator of neurologic functions by improving speed and skill in performance of tasks produced by the cerebral area to which it is reciprocally-connected. Such modulatory role over multiple brain regions appears compelling, mainly by considering the complexity of its reciprocal connections to common neural networks involved in motor, vestibular, cognitive, affective, sensory and autonomic processing. It is not known, however, how does the cerebellum contribute to migraine initiation, symptoms generation and headache. Specific cerebellar dysfunction trough genetically-driven excitatory/inhibitory imbalances, oligemia and/or increased risk to white matter lesions have been proposed as critical contributors to migraine pathogenesis. Given that neural projections and functions of many brainstem, midbrain and forebrain areas are shared between the cerebellum and migraine trigeminovascular pathways, this review will provide a synopsis on cerebellar structure and function followed by an update of relevant clinical and preclinical literature along with a scientific perspective on the potential role of cerebellar networks in migraine pathophysiology.